2021
DOI: 10.3390/jcm10071508
|View full text |Cite
|
Sign up to set email alerts
|

Tools for the Assessment of the Malnutrition Status and Possible Interventions in Elderly with Cardiovascular Diseases

Abstract: Malnutrition represents a common and important feature in elderly people affected by cardiovascular diseases. Several studies have investigated its prevalence and prognostic role in most clinical settings, including cardiovascular disease. However, in daily practice it usually remains unrecognized and consequently untreated. The present review was ideated to answer the main questions about nutritional status assessment in patients with cardiovascular disease: why, when, where, how to evaluate it, and what to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…9 This led to development of more comprehensive and objective assessment tools of nutritional status, controlling nutritional status (CONUT) score, prognostic nutritional index (PNI) score, geriatric nutritional risk index (GNRI) score, and mini nutritional assessment (MNA) score, which consider multiple biochemical parameters and anthropometric measurements to provide nutritional status. 10,11 GNRI is strictly designed for elderly patients according to their risk of malnutritional related complications, while CONUT and PNI are applied to all age groups based on biochemical parameters and can detect undernutrition at early stage. 12,13 The CONUT score is calculated based on serum levels of albumin estimating the protein reserve; total cholesterol levels estimating the caloric depletion and total lymphocyte count evaluating the level of impairment in immunity due to undernutrition.…”
Section: Introductionmentioning
confidence: 99%
“…9 This led to development of more comprehensive and objective assessment tools of nutritional status, controlling nutritional status (CONUT) score, prognostic nutritional index (PNI) score, geriatric nutritional risk index (GNRI) score, and mini nutritional assessment (MNA) score, which consider multiple biochemical parameters and anthropometric measurements to provide nutritional status. 10,11 GNRI is strictly designed for elderly patients according to their risk of malnutritional related complications, while CONUT and PNI are applied to all age groups based on biochemical parameters and can detect undernutrition at early stage. 12,13 The CONUT score is calculated based on serum levels of albumin estimating the protein reserve; total cholesterol levels estimating the caloric depletion and total lymphocyte count evaluating the level of impairment in immunity due to undernutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the clinical benefit of PCI therapy in SCAD patients seems to be limited to the relief of angina, reduction of the incidence of spontaneous myocardial infarction, and improvement of the survival quality of patients, without a significant impact on the long-term prognosis of SCAD patients, i.e., mortality [ 7 , 32 , 33 ], and therefore a large number of investigators are working to find clinical indicators that play an important role in the long-term prognosis of SCAD patients. Previous studies have shown that malnutrition is a common problem among hospitalized patients, and it is estimated that approximately 30-60% of hospitalized patients are at risk for malnutrition, with a higher prevalence in older hospitalized patients [ 14 , 34 ]. The presence of malnutrition risk may further weaken the immune system, and increase the cardiac burden and risk of infection in elderly patients with cardiovascular disease thereby prolonging hospitalization, with negative and far-reaching effects on clinical outcomes in elderly patients with SCAD [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Global Leadership Initiative on Malnutrition (GLIM) recommends a two-step approach that involves appraisal of the likelihood of malnutrition and its subsequent identification [ 31 ]. The Mini Nutritional Assessment (MNA) can be used to screen malnutrition [ 32 ]. However, the body mass index (BMI) may also be a useful proxy to assess nutritional status in older patients [ 33 ].…”
Section: Assessment Of Frailtymentioning
confidence: 99%